2018
DOI: 10.1002/ppul.23950
|View full text |Cite
|
Sign up to set email alerts
|

Impact of home spirometry on medication adherence among adolescents with cystic fibrosis

Abstract: Frequent home PFT monitoring is feasible in CF adolescents and could successfully improve medication adherence without significantly impacting treatment burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 39 publications
(106 reference statements)
2
27
2
Order By: Relevance
“…There was a small associated overall increase in medication adherence; MPR was 60% in the year prior to study enrolment, and 65% during the 12-month study period (p=0.038). These authors found no change in the number of exacerbations or FEV 1 decline between groups across the study period 33…”
Section: Digital Technology For Monitoring and Promoting Adherence Anmentioning
confidence: 89%
See 2 more Smart Citations
“…There was a small associated overall increase in medication adherence; MPR was 60% in the year prior to study enrolment, and 65% during the 12-month study period (p=0.038). These authors found no change in the number of exacerbations or FEV 1 decline between groups across the study period 33…”
Section: Digital Technology For Monitoring and Promoting Adherence Anmentioning
confidence: 89%
“…Adherence monitoring enables treatment guidance and allows clinicians to differentiate if changes in a patient’s condition are related to disease progression, attributable to poor adherence or a combination of the two. The impact of home monitoring on treatment adherence in adolescents and young adults has been explored in a before and after study using once weekly home monitoring and adherence monitoring using medication prescription refill data to calculate the medication possession ratio (MPR) 33. In comparison to Lechtzin’s eICE study, adherence to weekly spirometry monitoring was 59% which may reflect the impact of parental supervision in this population group.…”
Section: Digital Technology For Monitoring and Promoting Adherence Anmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of video conferencing alongside remote data collection via 'nonconnected' devices has also been explored [65], as have home-based lung function tests supported by regular telephone engagement with the clinical team [59]. These approaches have been shown to support improved adherence to treatment amongst patients [58].…”
Section: Cf Clinical Care Structure and Technologymentioning
confidence: 99%
“…[4][5][6] Our center has been involved in QI work for over 15 years. [7][8][9][10] QI work at our center has been partially supported by the Cystic Fibrosis Foundation (CFF) which has provided QI mentoring, teaching, and support.…”
Section: Introductionmentioning
confidence: 99%